Impact of different light colors in behavior, welfare parameters and growth performance of Fayoumi broiler chickens strain - HESHAM, M. H.; EL SHEREEN, A. H.; ENAS, S. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Light is considered one of the most managerial factors affecting poultry well-being. Therefore, the current study was conducted to investigate the effects of different light colors in behaviour, welfare and growth performance of Fayoumi chickens. A total of 300 one-day old chicks of Fayoumi broiler breed were weighed and randomly divided into 4 environmentally controlled chambers with different artificial light color (yellow, red, green and blue) until the end of the experimental period (12 weeks); each was divided into five replicate brooders (15 birds for each replicate). A scanning technique was used to report the chicken’s behaviors. Moreover, the plumage condition, foot and toe hyperkeratosis, foot and toe lesions (foot pad dermatitis) and growth performance were evaluated. Light colors had significant (P < 0.05) effects of the impose of different light colors in all kinds of behavior of Fayoumi chickens. It was found that eating frequency was the highest in blue light. Preening, dust bathing and drinking frequencies were the highest in green light. Birds reared in red light were more active, as expressed by greater walking, flying, head movement, litter scratching, body shaking, wing flapping, wing/leg stretching, feather pecking and aggression. While, birds in blue light were calmest, evidenced by more intense sleeping, sitting and idling behaviors. In spite of the fact that the light colors had no significant effect on plumage condition, health status of the foot and toe and growth performance, those parameters were better in birds kept in blue light than other light colors. We conclude that the blue light colour may improve the birds’ welfare.